Pengaruh Struktur Aktiva, Profitabilitas, Pertumbuhan Perusahaan dan Kebijakan Dividen terhadap Kebijakan Hutang - Dicky Afdi Prayogi; Budi Susetyo; Subekti (Faculty of Economics and Business, University of Pancasakti Tegal, 2016)
Influence of Asset Structure, Profitability, Corporate Growth and Dividend Policy on Debt Policy of basic and chemical industry manufacturing companies listed on Indonesia Stock Exchange. This study aims to determine the effect of Asset Structure, Profitability, Corporate Growth and Dividend Policy simultaneously and partially to the Debt Policy of manufacturing companies of the basic and chemical industry sectors listed on the Indonesia Stock Exchange. Data method used in this research is using purposive sampling by using criterion. Where data collection is processed using predetermined criteria. Based on the results of research: Simultaneously the asset structure, profitability, corporate growth and dividend policy together have a significant effect on debt policy. While partially Asset Structure has no effect on Debt Policy. Profitability has a negative and significant effect on the Company's Debt Policy. The Company's growth has no effect on the Company's Debt Policy. Dividend Policy has no effect on Company Debt Policy.